Clinical presentation of congenital adrenal hyperplasia in selected multiethnic paediatric population - Chellappah Thambiah, Subashini; Ahmad, Zalinah; Hambali, Zarida; Osman, Malina; Mohd Zain, Munira; Md Zain, Fuziah; Hong, Janet Yeow Hua (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
A clinical descriptive study was done to determine the sociodemographic, laboratory and clinical characteristics of patients with congenital adrenal hyperplasia (CAH) referred to Hospital Putrajaya, a tertiary endocrine centre in Malaysia. Electronic laboratory data of 51 CAH patients were obtained. The demographics and clinical details of the study population were acquired from a questionnaire completed by parents of participants. There were 25 males (49%) and 26 females (51%), of which, 58.8% were Malays. Median age of participants was 4 years whilst median age at diagnosis of CAH was two years. Parental consanguinity was documented in three patients (5.9%). Patients originated from Johor (19.6%), Selangor (19.6%), Negeri Sembilan (17.6%) and Kedah (13.7%). Majority of patients were diagnosed after one week of life (80.4%) although more females were diagnosed under the age of one week compared to males (p=0.041). Most females presented with ambiguous genitalia (42.3%) [p=0.001] whereas 72% of males presented with salt wasting (p=0.003). No significant associations between race and all other variables, though interestingly three Malay patients presented with ambiguous genitalia and hypertension. Equal gender distribution noted as expected in an autosomal recessive condition, although not in keeping with other Asian countries. Early diagnosis in females attributed to obvious genital ambiguity at birth. Varied clinical presentation, although in minority, necessitates genetic studies for prompt diagnosis and treatment. Considering that majority of patients presented with salt wasting and the age at diagnosis was delayed, the introduction of a neonatal screening programme is essential in Malaysia.